Mechanism and Treatment Strategy of Osteoporosis after Transplantation - Lei Song; Xu-Biao Xie; Long-Kai Peng; Shao-Jie Yu; Ya-Ting Peng (International Journal of Endocrinology)
Osteoporosis (OP) has emerged as a frequent and devastating complication of organ solid transplantation process. Bone loss after organ transplant is related to adverse effects of immunosuppressants on bone remodeling and bone quality. Many factors contribute to the pathogenesis of OP in transplanted patients. Many mechanisms of OP have been deeply approached. Drugs for OP can be generally divided into “bone resorption inhibitors” and “bone formation accelerators,” the former hindering bone resorption by osteoclasts and the latter increasing bone formation by osteoblasts. Currently, bisphosphonates, which are bone resorption inhibitors drugs, are more commonly used clinically than others. Using the signaling pathway or implantation bone marrow stem cell provides a novel direction for the treatment of OP, especially OP after transplantation. This review addresses the mechanism of OP and its correlation with organ transplantation, lists prevention and management of bone loss in the transplant recipient, and discusses the recipients of different age and gender.